2017
DOI: 10.1126/sciadv.1700398
|View full text |Cite
|
Sign up to set email alerts
|

Structural variants in genes associated with human Williams-Beuren syndrome underlie stereotypical hypersociability in domestic dogs

Abstract: We hypothesize that selection during dog domestication targeted CNVs associated with hypersociability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
195
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 156 publications
(210 citation statements)
references
References 101 publications
7
195
0
8
Order By: Relevance
“…However, in a modified Strange Situation Test experiment, Palmer and Custance (2008) noted a similar finding to ours: dogs did not show the stranger-wariness that was often seen in human infants. This result and ours are in line with recent work indicating that dogs might be hyper-social, and thus more likely to engage socially with strangers (von Holdt et al, 2017). Coupled with this genetic predisposition, early and continued socialization of Western dogs may produce a history of reinforcement in which any fear of strange people is diminished so that dogs will approach new people.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in a modified Strange Situation Test experiment, Palmer and Custance (2008) noted a similar finding to ours: dogs did not show the stranger-wariness that was often seen in human infants. This result and ours are in line with recent work indicating that dogs might be hyper-social, and thus more likely to engage socially with strangers (von Holdt et al, 2017). Coupled with this genetic predisposition, early and continued socialization of Western dogs may produce a history of reinforcement in which any fear of strange people is diminished so that dogs will approach new people.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, we previously found that access to the owner after a separation can be a reinforcer for domestic dogs (Feuerbacher & Wynne, 2016); the separation may be an aversive establishing operation and the reunion with the owner decreases that aversive motivation, after which the dog can then seek other reinforcers in the environment. These other reinforcers might be interacting with novel humans, which would align with the view that dogs are hyper-social (von Holdt et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The purposes for which humans have directed the development of dog breeds are varied, yet remain predictable across cultures. The natural canine attributes of visual and olfactory acuity (Chen, Irwin, & Zhang, 2012;Tacher et al, 2005), speed and endurance (Huson et al, 2012;Kemp, Bachus, Nairn, & Carrier, 2005;Pasi & Carrier, 2003), guardianship, predatory nature (Akkad et al, 2015;Starling, Branson, Thomson, & McGreevy, 2013;Sundman, Johnsson, Wright, & Jensen, 2016), and their seemingly innate companionability with humans (Cagan & Blass, 2016;Fadel et al, 2016;Gacsi, McGreevy, Kara, & Miklosi, 2009;vonHoldt et al, 2017;Jakovcevic, Elgier, Mustaca, & Bentosela, 2010;van der Waaij, Wilsson, & Strandberg, 2008) have been exploited for thousands of years. However, in the pursuit of a distinct lineage, selection of breeding animals will unavoidably rely on a small source pool (Alam et al, 2012;Calboli, Sampson, Fretwell, & Balding, 2008;Kumpulainen et al, 2017;Pfahler & Distl, 2015;Streitberger et al, 2012;Wijnrocx et al, 2016).…”
Section: Italian Dog Breedsmentioning
confidence: 99%
“…Most recently, the hypersociability in domestic dogs, as compared to wolves that have adapted to the coexistence with most dangerous humans, has been attributed to a genetic variant, akin to a human form of "pathological" hypersociability, known as Williams-Beuren Syndrome (vonHoldt et al, 2017). "This finding suggests that there are commonalities in the genetic architecture of WBS and canine tameness and that directional selection may have targeted a unique set of linked behavioral genes of large phenotypic effect, allowing for rapid behavioral divergence of dogs and wolves, facilitating coexistence with humans."…”
Section: Dogs Are Wolvesmentioning
confidence: 99%